A Cascade Strategy Enables a Total Synthesis of (−)‐Gephyrotoxin1. Issue 50 (16th October 2014) - Chu, Shuyu; Wallace, Stephen; Smith, Martin D.
Abstract A concise and efficient synthesis of (−)‐gephyrotoxin from L‐pyroglutaminol has been realized. The key step in this approach is a diastereoselective intramolecular enamine/Michael cascade reaction that forms two rings and two stereocenters and generates a stable tricyclic iminium cation. A hydroxy‐directed reduction of this intermediate plays a key role in establishing the required cis‐decahydroquinoline ring system, enabling the total synthesis of (−)‐gephyrotoxin in nine steps and 14 % overall yield. The absolute configuration of the synthetic material was confirmed by single‐crystal X‐ray diffraction and is consistent with the structure originally proposed for material isolated from the natural source.